MANIFESTATION OF AESTHETIC IDEAL IN AYBEK'S PROSE (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
The issue of aesthetic ideal in Oybek's works is one of the problems that our researchers have not yet found a solution for. In the works of the writer "Navoiy" and "Kutlug Khan" ideal images are more evident. In these works, the period, time and space are reflected in the plot of the work. The image of Navoi in the novel "Navoi" and the image of Yolchi in "Kutlug Khan" can be included as ideal images. Their character, portrait, and supporting characters serve to reveal the aesthetic ideal in the work.